Our love was a two-person game. At least until one of us died, and the other became a murderer: sexual homicide perpetrated by intimate partners. Issue 4 (20th August 2021) - Stefanska, Ewa; Bloomfield, Sinead; Carter, Adam
Abstract : Purpose: The analysis of previous studies showed that research pertaining to the examination of the crime scene and Modus Operandi variables in intimate partner homicide (IPH) is scarce. Additionally, to our knowledge, there are no studies investigating sexual homicide perpetrated by intimate partners. This study aims to address that void. Thus, the study examined various components of the crime event and as such, it was exploratory in nature. Design/methodology/approach: The study consisted of male sexual killers, who perpetrated against pubescent female victims (14 years old and over) and served a custodial sentence within Her Majesty's Prison Service in England and Wales. Variables for the study were chosen on the basis of previous research examining IPH and sexual homicide. Descriptive analyses were used in this exploratory study. Findings: Descriptive analyses indicated that the most prevalent aggravating circumstances in the lead up to the killing included conflict with the victim before the offence and substance use by the perpetrator around the time of the killing. Stalking was present in approximately a quarter of cases. The results of the analyses of sexual behaviours showed that in 54.9% of the sample the act of killing was purely instrumental whereas in 39.4% of the sample the underlying drive of the act of killing was closely related to the sexual aspect. Originality/value: This is a unique study on a topic not yet explored.